(untitled) (Journal of Pharmaceutical Negative Results, 2022)
We studied the dynamics of anthropometric indicators in 153 women of fertile age with Cushing's syndrome, who applied for excess weight, lack of menstruation and infertility in the RSSPMC of Endocrinology of the PHM of the Republic of Uzbekistan, from 2000 to the present. The control group consisted of 20 women with obesity of varying degrees and without menstrual irregularities.According to the classification of the American Association of Endocrinologists from 2012, all female patients with SC registered since 2000 (the dead are not included) were distributed according to etiology as follows: 1 g. - patients with ACTH-dependent CS– 115 (75.2%), 2 g. - with ACTH-independent CS - 35 (22.9%) and group 3 - patients with ACTH-ectopic CS - 3 (1.9%). 6 months after surgical and drug treatment, in groups 1 and 2 of patients there was a significant improvement compared with the average OT, OB, OT / OB data before treatment, while in patients of 3 groups there were significant changes in the average OT, OB, OT values / OB after 6 months of treatment not established.